UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA EDUKULBO PADA SISWA KELAS IV SDN 02 BENGKAYANG - Cindi Fernanda; Totok Victor Didik Saputro (STKIP Subang, 2026)
Mathematics learning in elementary schools still faces various challenges, particularly the low student learning outcomes caused by limited student involvement in the learning process and the lack of engaging instructional media. This condition was also found among fourth-grade students at SDN 02 Bengkayang, where mathematics achievement remained below the established minimum mastery criteria. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model assisted by Edukulbo media. The research employed a Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects were fourth-grade students of SDN 02 Bengkayang. Data were collected through observation and learning achievement tests. The research instruments included observation sheets for teacher and student activities as well as mathematics achievement test items. Data were analyzed using quantitative and qualitative descriptive techniques through the calculation of averages and learning mastery percentages. The results indicated that the implementation of the STAD cooperative learning model assisted by Edukulbo media successfully improved students’ mathematics learning outcomes. The improvement was reflected in the increase in the class average scores and the percentage of learning mastery in each cycle compared to the pre-action condition. Furthermore, student participation during the learning process increased as students became more actively engaged in discussions, collaboration, and classroom learning activities. Therefore, the STAD cooperative learning model assisted by Edukulbo media can be considered an effective alternative instructional approach for improving elementary school students’ mathematics learning outcomes, particularly in learning three-dimensional geometry concepts.